On the Treatment of a Patient with Ataxic Syndrome by Microdoses of Levo- and Carbo-Dopa. Post COVID Treatment - Tarro, G.; Raiderman, D. (British Journal of Healthcare and Medical Research, 2022)
The neurological evaluation and the report of the physioterapist are described for a patient who from 2018 was blocked by neurological status with different problems that concerned his different functions of the nervous systems on coordination and balance, motor exam and even speech, after the treatment with microdoses of Sinemet CR for two months. The satisfation is reported by the neurologist regarding the results on the patient recovery. Post COVID disorders are suggested to be treated with special indication for long COVID.